Do conventional and Islamic stock markets subject to different market anomalies? Empirical evidences from Indonesia and Malaysia - Abd. Majid, M. Shabri; Vakhira, Zulfa Alvi; Kassim, Salina (European Research Center of Managerial Studies in Business Administration, 2016)
This study aims to investigate whether the conventional and Islamic stock returns are subject to different calendar anomalies by testing the monthly calendar effects on stock returns in both markets. Focusing on the Indonesian and Malaysian Stock Markets, the closing monthly prices of the Jakarta Stock Exchange Index (JKSE), Kuala Lumpur Stock Exchange Index (KLSE), Jakarta Islamic Index (JII) and FTSE Bursa Malaysia Hijrah Shariah Index (FBMHS) were considered covering the period from 2004 to 2015. An independent sample of t-test is adopted to explore the differences between the conventional and Islamic stock returns in both countries, while the calendar effects of the stock returns are then tested using the multiple regression. The study finds that there were no differences between the conventional and Islamic stock returns, and the calendar anomaly is only existed in the Indonesian stock markets. This implies that although both the conventional and Islamic stock markets have been well integrated in both markets, the stock markets of Malaysia have been more efficient than the Indonesian counterpart.